دراسة الصفات الشكلية لحافرة أنفاق البازلاء Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae) وكثافتها العددية على نبات الفاصولياء في الساحل السوري - رمضان, علي; يوسف, مازن (Latakia University Journal -Biological Sciences Series, 2017)
بيّنت الدراسة الصفات المورفولوجية للطور الكامل لحشرة حافرة أنفاق البازلاء Liriomyza huidobrensis وكثافتها العددية على نبات الفاصولياء في مناطق مختلفة من الساحل السوري. لتعريف النوع L.huidobrensis تم اعتماد الحجم واللون، نظام تعريق الجناح الأمامي، الرأس وقرن الاستشعار، والصدر، والرجل الوسطى وآلة وضع البيض كصفات لتعريف الحشرة الكاملة الأنثى، ولتعريف اليرقة وأعمارها المختلفة تم اعتماد شكل وصفات هيكل الرأس البلعومي في طور اليرقة.بينت النتائج التطابق التام للنوع المعزول على نبات الفاصولياء في الساحل السوري مع المفاتيح التصنيفية المميزة للنوع، وبالتالي عدم تأثر الصفات المدروسة بالتوزع الجغرافي للنوع، وإن فترة ظهور الحشرة الكاملة لحافرة أنفاق البازلاء امتدت خلال 6 أشهر ابتداءً من شهر أيار وحتى تشرين الأول، حيث سُجّلت ذروة ظهورها خلال شهر حزيران في الخراب/طرطوس، وفي شهر تموز في موقعي بارمايا/بانياس والحويز/جبلة، مع ذروة متأخرة خلال شهر آب في محافظة اللاذقية في مزار القطرية والبهلولية، ليبلغ أعلى متوسط لغزارة الحشرة على نبات الفاصولياء في موقع الحويز/جبلة وبمعدل 0.8 حشرة/الورقة/الشهر، مع تأثير واضح للمعدل اليومي لدرجات الحرارة على اختلاف توزع هذه الغزارة.This study showed the morphological character of the adult of leaf miner Liriomyza huidobrensis and its seasonal abundance on the bean Phaseolus vulgaris in different location in the Syrian costal region. The research curried out in five location across costal region from beginning of May and end of December 2015. The definition of L. huidobrensis depended on: size and color of female adult, system vein of fore wings, head and antenna, thorax, and mid leg, ovipositor of female, and the definition the larva and its stages was depended on the mode of cephalopharyngeal skeleton. The results showed the complete correspond with the character of this kind that recognize it by using the identification key, so the morphological character of the adult of the Pea Leafminer L. huidobrensis doesn’t affected by the geographical destitution of kind.As the results showed the period of adult appearance of leaf miner extended for 6 month from May to December, with peak at June in the Alghrab\Tartos and July in the Barmaya\Baneas and Alhuez\Jablah and with a late peak at August in the Lattakia in Mazar-Alkatrea and Albahlulia, with a highest average of its density on bean in the Alhuez\Jablah 0.8\adult\leaf\month at July, with a clear effectiveness of the daily average of temperature on the distribution of its density .